1953
DOI: 10.1161/01.cir.8.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Coronary Occlusion

Abstract: The problem of the r'elationship between hypertension and coronary occlusion has been r'e-examined. Using newly established limits of hypertension, 600 consecutive private patients with coronary occlusion-500 men and 100 women-all under 65 years of age, were studied. Hypertension did not appear to be a factor in producing coronary disease and occlusion among men, but was a definite factor in its causation among women. The possible relation of the serum cholesterol, the Sf 12-20 lipoprotein fraction, and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1955
1955
1966
1966

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…Approximately 37 per cent of the males and 62 per cent of the females had a history of hypertension. These findings correspond well with those for hypertension in patients with myocardial infarction (22).…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 37 per cent of the males and 62 per cent of the females had a history of hypertension. These findings correspond well with those for hypertension in patients with myocardial infarction (22).…”
Section: Discussionsupporting
confidence: 88%
“…Thirty‐three (67 per cent) of the 49 females and twenty‐five (32 per cent) of the 78 males had a history of moderate to severe hypertension preceding the infarction. These results are in good agreement with the study of hypertension and coronary occlusion recently reported by Master (56). He found that 28 (70 per cent) of 40 women below the age of 55 with myocardial infarction had hypertension, and 26 per cent of the males with myocardial infarction before the age of 55 had a history of hypertension.…”
Section: Atherosclerosis and Coronary Heart Diseasesupporting
confidence: 93%
“…Although hypertension has usually been associated with increased atherosclerosis in both sexes, this has been especially true in women. 25 Hypertension in the men in our study was associated with an increased degree of atherosclerosis in their coronary and cerebral vessels, and with a greater occurrence of cardiac catastrophes. This association was even more marked, and involved more arteries, among women with hypertension.…”
Section: Hypertension and Atherosclerosissupporting
confidence: 44%